The Effect of Job Training and Compensation on the Performance of NCVS 2.02 Assembling Section Employees at PT Adis Dimension Footwear Balaraja-Tangerang - Febrianti, Siti Aulia; Cahyono, Yoyok; Umam, Akhmad Hairul (Faculty of Science and Technology University of Pramita Indonesia, 2025)
The purpose of this study was to determine how much influence job training and compensation have on the performance of employees in the Assembling NCVS 2.02 section at PT Adis Dimension Footwear, Tangerang Regency.This study uses a quantitative descriptive method, namely research that describes variables as they are supported by data in the form of numbers generated from actual conditions. The population in this study were all employees in the Assembling section at PT Adis Dimension Footwear, Tangerang Regency. The research sample consisted of 83 respondents. This study used a saturated sample technique because the population was small, so the sample in this study used the entire population to be used as respondents, as many as 83 employees.The results of this study indicate that (1) partially, job training significantly influences the performance of employees in the Assembling NCVS 2.02 section at PT Adis Dimension Footwear, Tangerang Regency, as indicated by the calculated t value> t table (5.310 > 1.990) and a significance value of 0.000 which is smaller than the significance value of 0.05. Thus, Ha is accepted and H0 is rejected. (2) Partially, compensation significantly influences the performance of employees in the Assembling NCVS 2.02 section at PT Adis Dimension Footwear, Tangerang Regency, as indicated by the calculated t value > t table (6.578 > 1.990) and a significance value of 0.000 which is smaller than the significance value of 0.05. Thus, Ha is accepted and H0 is rejected. (3) Simultaneously, job training and compensation significantly influence the performance of employees in the Assembling NCVS 2.02 section at PT Adis Dimension Footwear, Tangerang Regency, as indicated by Fcount> Ftable (114.329>3.11) with a significance level of 0.000, thus Ha is accepted and H0 is rejected.Based on the results of the study, it can be concluded that job training and compensation variables, both partially and simultaneously, have a significant influence on the performance of employees in the Assembling NCVS 2.02 section at PT Adis Dimension Footwear, Tangerang Regency.